Flow: The Urban Landscape Around the Itapemirim River - Souza, João Wesley de; Xavier, Ana Carolina (Farol, 2025)
This article critically analyzes the urban landscapes formed along the course of the Itapemirim River, from its headwaters in the Serra do Caparaó to its mouth in the Atlantic Ocean. Through an observational and reflective approach, the article contrasts the exuberance of natural landscapes with the process of urban and architectural degradation. The causes of this degradation are discussed, highlighting the lack of effective action by architecture and urban planning professionals. Finally, the article proposes the need for public policies that bring these professionals closer to the social and territorial realities of local populations.
Keywords: urban landscape; architectural degradation; urban memory